Comparative microbial diversity and redox environments of black shale and stromatolite facies in the Mesoproterozoic Xiamaling Formation - Luo, G.; Hallmann, C.; Xie, S.; Ruan, X.; Summons, Roger (Elsevier Ltd, 2015)
© 2014 Elsevier Ltd. The composition of microbial communities and their relationship to ocean redox structure in the Precambrian are topics of continuing interest in geobiology. Our knowledge of organismic diversity and environmental conditions during this time are mostly based on fragmentary paleontological and geochemical records and might be skewed accordingly. In North China the Xiamaling Formation (~1.37Ga) is characterized by black shales of relatively low thermal maturity (Tmax is ~445°C) and has been identified as a potential petroleum source rock. To date, however, the biological sources of the organic matter and the environmental conditions prevalent during the deposition of these sediments remain unclear. In this study we analyzed the hydrocarbon biomarker compositions of the Xiamaling Formation shales and a superjacent stromatolitic carbonate in order to shed light on the microbial diversity in the sedimentary environments they represent. The hydrocarbons extracted from both sediments are dominated by low-molecular-weight n-alkanes with a maximum at C15-18, suggesting that bacteria and/or algae were primary biotic precursors. Our inability to detect steranes in bitumen I, and only traces of rearranged steranes in bitumen II of black shales, indicates that modern eukaryotic algae were either ecologically insignificant or not preserved due to a taphonomic bias. The high relative concentration of hopanes and diahopanes ranging from C27 to C35, as well as monomethylalkanes, suggests that cyanobacteria may have been the dominant primary producers and could have contributed to the biologically available nitrogen pool through N2-fixation. This observation is supported by the low nitrogen isotopic composition of the kerogens. Even though all facies zones appear to have been anoxic but not sulfidic on the basis of biomarker ratios and trace metals, subtle but distinct molecular differences are observed between the stromatolite and the black shales, which can be attributed to both, lithologically-controlled diagenetic rearrangements and differential biotic input. The discrepancy between the presence of a large UCM and high abundances of alkyl lipids on one hand, yet the absence of a stable carbon isotopic offset between lipids and kerogen, on the other, suggests that strong heterotrophic reworking might not be the sole source of the biodegraded fingerprint that is so typical for Proterozoic bitumens, and demands alternative explanations.